Oestrogen treatment of constitutional tall stature: a risk-benefit ratio. Issue 2 (1st February 1998) - Weimann, E; Bergmann, S; Böhles, H J
Abstract : Oestrogens are given in high doses for the treatment of tall stature in girls. The aim of this study was to obtain data considering efficiency, side effects, and acceptance of the treatment of 50 constitutionally tall girls treated with conjugated oestrogens (7.5–11.25 mg/day). The mean (SD) adult height predictions were 188.3 (4.4) cm and the achieved height was 5.2 (3.3) cm less than the predicted height. A greater reduction from final predicted height occurred when treatment was started at an early bone age (<13.0 years) and with a remaining growth potential of greater than 10 cm. Even postmenarcheal girls, however, had a mean reduction of 4.8 (3.2) cm. The main side effects were considerable weight gain (>10 kg), an increase in triglyceride concentrations (37.5% of the patients), and increased platelet aggregation (60% of the patients). Altogether 84.6% of the patients were satisfied with the treatment and 15.4% regretted having had it.